Automated technology for verification and analysis : 14th International Symposium, ATVA 2016, Chiba, Japan, October 17-20, 2016, Proceedings /: 14th International Symposium, ATVA 2016, Chiba, Japan, October 17-20, 2016, Proceedings. (2016) - Unknown
No abstract available